Cover Picture: Asymmetric Ketone Reduction by Imine Reductases (ChemBioChem 3/2017). (16th January 2017) - Lenz, Maike; Meisner, Jan; Quertinmont, Leann; Lutz, Stefan; Kästner, Johannes; Nestl, Bettina M.
Abstract : The cover picture shows a recently discovered imine reductase (IRED) planet in the outer space of enzyme biocatalysts. The carbonyl‐reducing enzyme family of β‐hydroxyacid dehydrogenases (βHAD) orbits the planet as blue moon demonstrating their evolutionary relatedness to IREDs. We investigated the promiscuity of IREDs for ketone reduction by elucidating the electronic effects of substituents on substrate molecules and their influence on catalysis. The IRED activity for the examined substrates is illustrated by the distance of the constellations to the planet. The authors identified a "substrate rocket" by substitution of the keto functionality by a trifluoromethyl group. We are grateful to Richard Mensah for the graphic design of the cover. More information can be found in the Communication by B. M. Nestl et al. onpage 253 in Issue 3, 2017 (DOI:10.1002/cbic.201600647 ).